Identification and characterization of the water gap in the physically dormant seeds of Dodonaea petiolaris: A first report for Sapindaceae - Turner, S.; Cook, A.; Baskin, J.; Baskin, C.; Tuckett, R.; Steadman, K.; Dixon, Kingsley (Oxford University Press, 2009)
Background and AimsThe Sapindaceae is one of 17 plant families in which seed dormancy is caused by a water-impermeable seed or fruit coat (physical dormancy, PY). However, until now the water gap in Sapindaceae had not been identified. The primary aim of this study was to identify the water gap in Dodonaea petiolaris (Sapindaceae) seeds and to describe its basic morphology and anatomy.MethodsSeed fill, viability, water-uptake (imbibition) and other characteristics were assessed for D. petiolaris seeds. The location and structure of the water gap were investigated using a blocking experiment, time series photography, scanning electron microscopy and light microscopy. Dodonaea petiolaris seeds with PY also were assessed for loss of PY at four ecologically significant temperatures under moist and dry conditions. Seeds of three other species of Sapindaceae were examined for presence of a water gap.Key ResultsThe water gap in D. petiolaris seeds was identified as a small plug in the seed coat adjacent to the hilum and opposite the area where the radicle emerges. The plug was dislodged (i.e. water gap opened = dormancy break) by dipping seeds in boiling water for 2·5 min or by incubating seeds on a moist substrate at 20/35 °C for 24 weeks. Layers of cells in the plug, including palisade and subpalisade, are similar to those in the rest of the seed coat. The same kind of water gap was found in three other species of Sapindaceae, Diplopeltis huegelii, Distichostemon hispidulus and Dodonaea aptera.ConclusionsFollowing dormancy break (opening of water gap), initial uptake of water by the seed occurs only through the water gap. Thus, the plug must be dislodged before the otherwise intact seed can germinate. The anatomy of the plug is similar to water gaps in some of the other plant families with PY.